Electromyographic analysis of the masseter and temporalis muscles and bite force in a patient treated by functional maxillary orthopedics: a case report (Indian Journal of Case Reports, 2016)
This case report evaluated electromyographic activity of the masseter and temporalis muscles and molar bite force, before and after with functional orthopedic. A 65 years woman presenting with orofacial pain symptoms, cervical tension, condyle subluxation and osteoarthrosis. The patient was diagnosed with temporomandibular dysfunction and treated with use of a Simões Network 9 modified type functional maxillary orthopedics appliance. The Myosystem BR1 apparatus was used to analyze the electromyographic activity of the masseter and temporalis muscles. The maximum molar bite force was measured with the digital dynamometer (Kratus). This study showed increased EMG activity of the masseter and temporalis muscles in postural conditions of mandible and molar bite force after 12 months of treatment. After twelve months of treatment, the patient had lack of pain symptoms as well as an improvement in the balance of the mastication muscles, as demonstrated by EMG activity and maximum molar bite force.